Mengurai Permasalahan Audit Syariah dengan Analytical Network Process(ANP) - Taufik Akbar; Sepky Mardian; Syaiful Anwar (Jurnal Akuntansi dan Keuangan Islam, 2015)
Shariah audit had an important role in maintaining shariah compliance for an shariaentity in this case of shariah banking considering encouraging its development todriven away. So that the problem on an audit shariah bring negative effects evenfailure in fulfilling will shariah principle itself. In order to overcome these issues ,research it expresses priorities of the problems and priorities solution pertaining toaudit shariah. While methods used in research is known as analytic network process(ANP) where the data primarily obtained through in depth interviews with expertsshariah audit derived from academics and practitioner. The result of this research fromthe side of the problems of shariah audit that the regulations and the audit aspect standard shariah inadequate be the main problems. In terms of solution audit shariahshow that the solution regulations with its aspect which is to build sop supervision aspart of internal control to be the solution main.